Identification of Gene Variations and Gene Expression in Allergic Diseases Using a Bioinformatics Approach - Naila Ismatun Hasanah; Ilham Alifiar; Rahmawati (Jurnal FARMASIMED (JFM), 2026)
Background: Allergy is an abnormal or excessive immune response to allergens involving complex interactions between genetic and environmental factors. Identification of genetic variations contributing to allergy susceptibility is important to understand molecular mechanisms and support the development of personalized biomarkers and therapies. Objective: This study aimed to identify genetic variations and gene expression profiles associated with allergic diseases using a bioinformatics approach. Research Methods: The study was conducted using a bioinformatics approach by analyzing data from GWAS Catalog, HaploReg v4.2, SNPnexus, GTEx Portal, and Ensembl Genome Browser. Results: A total of 18 missense single-nucleotide polymorphism variants are associated with allergic diseases. Three variants, namely rs1805009 (MC1R), rs183884396 (TESPA1), and rs59039403 (NLRP10), show the highest prediction score (1.000), indicating the most significant biological impact. Gene expression analysis shows dominant expression in whole blood, EBV-transformed lymphocytes, and skin (sun-exposed). Conclusion: The identified missense variants potentially contribute to the pathogenesis of allergic diseases and may serve as a basis for the development of genetic biomarkers and personalized therapeutic approaches.